Effect of graded levels of nitrogen on plant height and flower yield of Jasmine (Jasminum sambac L.) cv. Local in the Batticaloa district - Srikrishnah, S.; Thamotharampillai, T.; Sutharsan, S. (University of Jaffna, 2015)
An experiment was carried out to evaluate the effects of graded nitrogen levels on plant height and flower yield of Jasmine (Jasminum sambac L.) cv. Local in Batticaloa district. Graded levels of nitrogen were defined as treatments viz. 0 (T1), 50 (T2), 100 (T3), 200 (T4), 300 (T5), and 400 (T6) g of nitrogen/plant/year. Nitrogen was applied at monthly interval. Phosphorous and potassium levels were be kept constant throughout the experiment and applied as basal dressing. The experiment was arranged in a completely randomized design with three replications. Agronomic practices were followed uniformly for all treatments. Plant height and flower yield were measured at monthly interval. Analysis of Variance was performed to determine significant difference among treatments (p < 0.05). Results indicated that plant height and flower yield were significantly higher in T4. Plants grown at this nitrogen level would have received optimum amount of nitrogen. Therefore growth and flower production of Jasmine was higher at this treatment. From this experiment, it could be stated that nitrogen level of 200 g/plant/year is optimum for growing Jasmine in dry zone since growth and flower yield were higher.
Keywords: Flower yield; Jasmine; Nitrogen level; Plant height